2020
DOI: 10.3390/antiox9020187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Selenium Biofortification on Antioxidant Properties and Phenolic Compounds of Apples (Malus domestica)

Abstract: Biofortified apples seem to be a suitable produce. In this study, different selenium forms and application levels were applied to the two apple varieties ‘Golden Delicious’ and ‘Jonagold’, grown in the years 2017 and 2018 in order to increase the selenium uptake within a typical Western diet. It was shown that the biofortification, which was performed as a foliar application implemented in usual calcium fertilization, led to significantly increased selenium contents in the fruits. Furthermore, biofortification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 66 publications
(130 reference statements)
2
46
0
1
Order By: Relevance
“…It is hypothesized that the application of selenium-containing fertilizers leads to the better protection of the fruits against certain stress factors, whereby only a lower synthesis rate of the Mal d 1 protein is required. The induction of further plant-protective substances, such as phenolic compounds, resulting from biofortification with selenium in apples [ 48 ] and other crops [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ] has also been determined in previous studies. Furthermore, it has already been shown that selenium can protect plants from a range of abiotic stresses such as cold, drought, radiation, salinity, and heavy metals [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that the application of selenium-containing fertilizers leads to the better protection of the fruits against certain stress factors, whereby only a lower synthesis rate of the Mal d 1 protein is required. The induction of further plant-protective substances, such as phenolic compounds, resulting from biofortification with selenium in apples [ 48 ] and other crops [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ] has also been determined in previous studies. Furthermore, it has already been shown that selenium can protect plants from a range of abiotic stresses such as cold, drought, radiation, salinity, and heavy metals [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the influence of the biofortification of apples with selenium by foliar fertilization was investigated. There, it was found that the content and composition of phenolic compounds were significantly influenced by selenium [ 48 ]. In other experiments it was found that even the Mal d 1 content was reduced, in most cases, when the fruits were biofortified with selenate, while apple cultivar and ecophysiological conditions (e.g., climate) were identified as further influencing factors [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, at a content of 50 μg I (100 g FM) –1 , the target value for Se would be 5.2 μg (100 g FM) –1 . In a study by Groth et al (2020) , Se content of this level was achieved in apples by a foliar spray of 150 g Se (ha ⋅ m CH) –1 , regardless of whether SeO 3 2– or SeO 4 2– was applied. Further field experiments are needed to examine the effects of appropriately increased Se fertilization rate in combination with I.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the effect of chemical stress induced by selenium treatment can enhance the antioxidant activity of plant extracts [38,43]. However, the opposite results are also reported [44]. The two studied varieties of apples were differently affected: one of them mostly showed a higher antioxidant activity (measured with TEAC) resulting from the biofortification and independently of the selenium form and the level of application, whereas the values for the second was only slightly influenced by the biofortification.…”
mentioning
confidence: 91%